PENGELOLAAN SAMPAH ORGANIK MENGGUNAKAN MIKROORGANISME - Oom Komala; Dewi Sugiharti; Rouland Ibnu Darda (Ekologia: Jurnal Ilmiah Ilmu Dasar dan Lingkungan Hidup, 2012)
The study of organic waste using microorganisms has been carried out, aiming to find the concentration of microorganisms that can deodorize and can degrade organic waste into compost and fertilize the plants. The method used for waste is experimental with 4 treatment is not given microbe, 25 ml microbe concentrations of 106, 50 ml microbe concentrations of 106 and 75 ml microbe concentration of 106 under anaerobic conditions. After 20 days of fermenting compost is given at 1 month age chilli crop at a dose of 15 g per week for 5 weeks. Waste parameter includes aroma, pH, texture and temperature. In chilli crop plant height, number of leaves, fresh weight and dry weight, were analyzed using factorial completely randomized design 4x4 to see the influence ofÂ  crops. The results can be seen that organic waste can be managed using a mix of microbes into compost that can improve plant growth chillies with a dose of 25 ml concentrations of 106 of the best.